Raman assisted X-Ray crystallographic study of nitric oxidebinding to deoxygenated hemoglobins - PICA, ANDREA; MERLINO, ANTONELLO; VERGARA, ALESSANDRO; Anna Balsamo; Lelio Mazzarella (IUCr, 2011)
Nitric oxide (NO) is a signaling molecule that regulates essential physiological processes, including neurotransmission, vasodilatation, and blood clotting [1]. The heme groups of deoxy hemoglobin (Hb) bind NO very strongly, almost irreversibly, with a Kdiss = 0.9 x 10-12 M. The kinetic constant of NO dissociation from Hb(NO)4 increases as the reaction progresses, indicating that partially NO-saturated T-state Hb has a lower NO affinity than fully bound, R-state, Hb [2]. Previous spectroscopic and crystallographic studies have shown that NO binding to the heme groups of T-state human hemoglobin (HbA) produces the breakage of Fe-proximal histidine bonds at the α- subunits but not at the β-subunits [3]. NO can also react with the thiol group of the Cys93β of HbA [4]. Until now there are very few crystallographic structures of nitrosylhemoglobin, due to the high and various reactivity of these species. Here we report a Raman-assisted crystallographic study of the NO binding to the hemoglobin isolated from the Antarctic fish Trematomus bernacchii (HbTb). HbTb is endowed with the Root effect, i.e. a drastic drop of cooperativity at acidic pH [5,6]. The crystal structures of the nitrosylated form of T-state HbTb, crystallized at pH 6.2 and 8.4 (HbTb6NO and HbTb8NO), have been solved. These structures and the Raman spectra have been compared to those of nitrosylated HbA, reported in literature [3,7]. The main results of the analysis reveal a different behavior of α and β chains. In particular, in both HbTb6NO and HbTb8NO, the α-heme is nitrosylated and shows a six-coordination, whereas the iron ion at β-heme is clearly oxidized in high spin form.